Theoretical Study of the Effect of the Coupling Constant Strength on the Photons Rate Yield for Quark Gluon Interaction - Hadi J. M. AL-Agealy (University of Thi-Qar Journal of Science, 2019)
Rate of photon yield in a quark-gluon interaction exhibits of the coupling constant strength and temperature dependence have been studied theoretically .The estimation of the coupling constant strength is very important tool for the investigation of the QCD, which has been applied to the dynamical quarks = 3, 5, ,and gluon = 0 . Depending upon the the coupling constant data ,it shows that the strong force is relatively weak for quarks, and the two quarks move farther apart the force becomes stronger. The weakness of interaction at short distance is called asymptotic freedom, while the strength of the long distance is called confinement .Rate of the photon yield in a quark-gluon interaction which investigation due to the electric charge of the quark with color quantum number. Photon’s rate has been calculated increasing with increases in temperature and decreasing the coupling constant and photon’s yield from the system has height fever number larger than system has low fever number